Work-family conflict in a cohort of Italian nurses. An observational, multicenter, cross-sectional study: Work-family conflict in a cohort of Italian nurse - Carvello, Maicol; Lupo, Roberto; Cicognani, Corin; Conte, Luana; Artioli, Giovanna; Vitale, Elsa; Rubbi, Ivan (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work: Work-family and family-work conflict can be defined as the degree to which participation in one role, in this case as a worker, interferes with the ability to cope with the responsibilities of another role, namely that of a member of a household. The aim of the study is to investigate the presence of indicators of work- family and/or family-work conflict in a cohort of Italian nurses and possible correlations with social and work variables. Research design and Methods: An observational, quantitative, multicenter survey was conducted for the study through the computerized administration of a validated questionnaire (Work-Family and Family-Work Conflict, CLF), with the implementation of sociographic variables. The cooperation of 15 Orders of Nursing Professions throughout the country was sought for sample collection. Data collection was bimonthly. Results: Among the participating nurses, there is a statistically significant predominance of conflict in the family-work direction. In particular, the phenomenon seems to be related to age and the presence of children and/or elderly at home to care for. Some work variables seem to positively affect the prevention of potential work-life conflict, such as rostering and work articulation. Conclusions: These findings place emphasis on the need for healthcare organizations to address the work-family balance of their employees.